ASIMETRI INFORMASI DALAM MEMODERASI PENGARUH KESESUAIAN KOMPENSASI, MORALITAS MANAJEMEN, DAN ETIKA KEPEMIMPINAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Pratiwi, Risti; Mulyani, Susi Dwi; Hamzah, Noravida (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
This study aims to analyze the effect of suitability of compensation, management morality, leadership ethics, on the tendency of accounting fraud with information asymmetry as a moderating variable. The population in this study are employees of companies located in the Greater Jakarta area. The technique used in sampling is to use purposive sampling with the criteria of employees working in the accounting field, having worked for more than one year and participating in preparing the company's financial statements. Data collection in this study was carried out using a questionnaire. This study uses the SPSS program assisted by MS Excel as an analytical tool. The research results show that the appropriateness of compensation does not affect the tendency of accounting fraud, management morality has a negative effect on the tendency of accounting fraud, ethical leadership has no effect on the tendency of accounting fraud, information asymmetry does not weaken the effect of appropriateness of compensation on the tendency of accounting fraud, information asymmetry can weaken the effect of management morality on accounting fraud tendencies, and information asymmetry cannot weaken the influence of ethical leadership on accounting fraud tendencies.